Implementation UMK Determination Based on Minister of Manpower Regulation Number 16 of 2024 at the Manpower and Transmigration Service of East Java Province - Shinta Dwi Febia Kumalasari; Magda Faradiba (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Abstract The determination of the Regency/City Minimum Wage (UMK) is an important step in protecting workers and maintaining business stability. The government has issued Minister of Manpower Regulation No. 16 of 2024 as the basis for calculating the 2025 UMK, taking into account economic growth, inflation, and certain indices. This study aims to analyze the implementation of this policy using George C. Edwards III's implementation theory, which covers aspects of communication, resources, implementer disposition, and bureaucratic structure. The method used in this study is a descriptive qualitative approach through interviews, observation, and documentation. The results of the study show that the policy communication process is already underway, but it is not yet evenly distributed, causing differences in understanding between regions. Human resources are quite competent, but budget constraints and the vastness of the region hinder socialization and supervision. The attitude of the implementers is supportive, but differences in interests between workers and employers affect the UMK determination process. The bureaucratic structure is functioning, but it does not fully follow the formula due to socio-political considerations. In general, the implementation of the 2025 UMK in East Java is not yet fully in accordance with Permenaker No. 16 of 2024, so integrated supervision, strengthening of human resources, and more optimal dissemination are needed.